Betaine addition to the diet alleviates intestinal injury in growing rabbits during the summer heat through the AAT/mTOR pathway - Zimei Li; Junning Pu; Xiang Chen; Yanbin Chen; Xiaoyan Peng; Jingyi Cai; Gang Jia; Hua Zhao; Gang Tian (Journal of Animal Science and Biotechnology, 2024)
Abstract Background The aim of this experiment was to investigate the effect of different levels of betaine (Bet) inclusion in the diet on the intestinal health of growing rabbits under summer heat. A total of 100 weaned Qixing meat rabbits aged 35 d with body weight of 748.61 ± 38.59 g were randomly divided into 5 treatment groups: control group (basal diet) and Bet groups (basal diet + 0.75, 1.0, 1.5 or 2.0 g/kg Bet). The average daily temperature in the rabbitry during the experiment was 30.48 °C and the relative humidity was 69.44%. Results Dietary addition of Bet had no significant effect on growth performance and health status of growing rabbits (P > 0.05), but it increased ileal secretory immunoglobulin A content compared to the control under summer heat (P < 0.05). Addition of 0.75 g/kg Bet up-regulated jejunal IL-4, down-regulated ileal TNF-α expression (P < 0.05). The addition of 1.0 g/kg Bet increased the villi height (VH) in the jejunum (P < 0.05). Serum glucose levels were reduced, and the expression of SLC6A20 was up-regulated in jejunum and ileum of rabbits fed with 1.5 g/kg Bet (P < 0.05). When added at 2.0 g/kg, Bet reduced serum HSP70 content, increased jejunal VH, and up-regulated duodenal SLC7A6, SLC38A2, mTOR and 4EBP-2 expression (P < 0.05). Correlation analysis revealed that intestinal mTOR expression was significantly and positively correlated with SLC7A6, SLC38A2, SLC36A1 and IL-4 expression (P < 0.05). Conclusions Dietary addition of Bet can up-regulate the expression of anti-inflammatory factors through the AAT/mTOR pathway, improve the intestinal immune function, alleviate intestinal damage in growing rabbits caused by summer heat, and improve intestinal health.